2008
DOI: 10.1158/1535-7163.mct-07-0434
|View full text |Cite|
|
Sign up to set email alerts
|

Sensitizing estrogen receptor–negative breast cancer cells to tamoxifen with OSU-03012, a novel celecoxib-derived phosphoinositide-dependent protein kinase-1/Akt signaling inhibitor

Abstract: Tamoxifen is a mainstay in the treatment of estrogen receptor (ER) -positive breast cancer patients. Although the efficacy of tamoxifen has been attributed to induction of tumor cell growth arrest and apoptosis by inhibition of ER signaling, recent evidence indicates that tamoxifen possesses ER-independent antitumor activities. Here, we use OSU-03012, a small-molecule inhibitor of phosphoinositide-dependent protein kinase-1 (PDK-1) to address the hypothesis that PDK-1/Akt signaling represents a therapeutically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 32 publications
1
71
0
Order By: Relevance
“…However, the overall tumour volume was only decreased by 49% as compared with control after EGCG þ curcumin treatment, indicating that EGCG þ tamoxifen is a more effective combination therapy as tumour volume was decreased by 71% as compared with control. Another recent study has shown that ER-negative breast cancer cells can be sensitised to the effects of tamoxifen by using a PDK-1/ Akt inhibitor (Weng et al, 2008). In this study, tamoxifen (60 mg kg À1 ) was unable to suppress the growth of MDA-MB-231 xenografts, but the addition of OUS-03012 (100 mg kg À1 ) showed significant tumour suppression (decreased 50% in control).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…However, the overall tumour volume was only decreased by 49% as compared with control after EGCG þ curcumin treatment, indicating that EGCG þ tamoxifen is a more effective combination therapy as tumour volume was decreased by 71% as compared with control. Another recent study has shown that ER-negative breast cancer cells can be sensitised to the effects of tamoxifen by using a PDK-1/ Akt inhibitor (Weng et al, 2008). In this study, tamoxifen (60 mg kg À1 ) was unable to suppress the growth of MDA-MB-231 xenografts, but the addition of OUS-03012 (100 mg kg À1 ) showed significant tumour suppression (decreased 50% in control).…”
Section: Discussionmentioning
confidence: 59%
“…This concept has been shown by combining docetaxel, genistein, black cohosh, and palm oil tocotrienols (Ferlini et al, 1997;Guthrie et al, 1997;Tanos et al, 2002;Bollig et al, 2005;Al-Akoum et al, 2007) with tamoxifen, which elicited cytotoxicity, apoptosis, and G1 arrest in various ERnegative breast cancer cell lines. Recently, this has been shown in both MDA-MB-231 cells and a xenograft model by combining tamoxifen with OSU-03012, a phosphoinositide-dependent protein kinase-1/Akt inhibitor (Weng et al, 2008). Our laboratory has also used ER-negative breast cancer cells to demonstrate that a combination of epigallocatechin gallate (EGCG) and tamoxifen elicits synergistic cytotoxicity (Chisholm et al, 2004).…”
mentioning
confidence: 99%
“…OSU-03012 has been shown to induce apoptosis in non-small cell lung cancer (26) and breast cancer cells (27,28) through inhibition of PDK/AKT signaling pathway. However, only very limited PDK1 and AKT inhibition were detected in OSU-03012-treated Huh7 cells in this study, suggesting that OSU-03012 suppresses the growth of Huh7 cells through a mechanism different from PDK1 and AKT inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of OH-TAM to ERa leads to a decrease in tumor cell growth [6]. OH-TAM is also effective in the absence of ER expression in breast cancer, melanoma, glioma and pancreatic carcinoma [7][8][9]. However this non-genomic effect (i.e.…”
Section: Introductionmentioning
confidence: 99%